Review of Recent Advances in the Physiology of the Regulation of Cellulase and Xylanase Production by Basidiomycetes - Vladimir Elisashvili; Eka Metreveli; Tamar Khardziani; Kakha Sokhadze; Aza Kobakhidze; Eva Kachlishvili (Energies, 2023)
The potential of wood-rotting and litter-deconstructing basidiomycetes to convert lignocellulose into a wide variety of products has been extensively studied. In particular, wood-rotting basidiomycete secretomes are attracting much attention from researchers and biotechnology companies due to their ability to produce extracellular hydrolytic and oxidative enzymes that effectively degrade cellulose, hemicellulose, and lignin of plant biomass. An analysis of the available literature data shows that Basidiomycota fungi, which are most adapted to the depolymerization of plant polysaccharides, are promising but so far unexploited sources of new hydrolytic enzymes. The review summarizes the latest data on the great variety, common features, and unique properties of individual fungi and the production of cellulases and xylanases by various physiological and ecological groups of basidiomycetes. The most important microbial cellulase-producing strains for submerged and solid-phase fermentation, as well as the main substrates, including the use of agro-industrial waste, are considered. It highlights ways to increase both cellulase and xylanase expression levels and the cost-effectiveness of producing these enzymes for various biotechnological applications. It is anticipated that this review will be particularly useful to novice scientists working in the lignocellulose biorefinery, as it describes current knowledge and issues related to the production and regulation of polysaccharide hydrolyzing enzyme synthesis.